Performance evaluation of attached biofilm reactors for the treatment of wastewater contaminated with aromatic hydrocarbons and phenolic compounds. Issue 4 (August 2017) - Oberoi, Akashdeep Singh; Philip, Ligy
Graphical abstract: Highlights: Performance of MBBR and SABF at different operation conditions was evaluated. MBBR shows relatively high stability against hydraulic and organic shock loads. Phenol and cresol at high concentration impacted the removal of other hydrocarbons. Effluent toxicity was monitored using bacterial bioassay. Biofilm constituents showed significant variation with varied operating conditions. Abstract: The present study investigated the performance of single stage moving bed biological reactor (MBBR) and submerged aerated biological filter (SABF) for the treatment of wastewater contaminated with heterocyclic and homocyclic aromatic hydrocarbons along with phenolic compounds commonly discharged from coal and biomass gasification plants. Performance evaluation of both the bioreactors was carried out by varying hydraulic and organic loading rates (OLR). Removal efficiencies (R.E) of 90.4 ± 0.78% and 85.8 ± 1.96% were achieved in MBBR and SABF, respectively at HRT of 24 h and OLR of 2.45 kg/m 3 /day. Increasing the OLR to 4.77 kg/m 3 /day resulted in the reduction of R.E of MBBR and SABF to 86 ± 0.96% and 77.8 ± 1.45%, respectively. MBBR showed better stability against hydraulic and organic shock loads in comparison to SABF. The effect of co-contaminants such as phenol and cresol on overall reactor performance was also investigated. The coexistence of phenol (300 mg/L) and cresol (100 mg/L) affected the removal of other hydrocarbons and resulted in accumulation of the metabolic intermediates. TOC R.E was 86.8% and 84.9% while reduction in toxicity was 61% and 57% in MBBR and SABF during simultaneous treatment of mixed hydrocarbons and phenolic compounds (OLR = 3.43 kg/m 3 /day, HRT = 24 h). Modified Stover- Kincannon model was incorporated to elucidate the substrate utilization kinetics. Characterization of attached biofilm on the carrier elements showed a significant variation in extracellular polymeric constituents with different pollutant concentrations.